The Influence Authentic Leadership on Affective Commitment of Members at the One Indonesian Charity Institution - Sandi, Silvia Anggraini Ana; Yudiani, Ema (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Human Resource Management (HRM) is still a challenge for companies and organizations, one of which is to increase organizational commitment to members which has an impact on competitive advantage where the role of leaders is needed to increase commitment to members. Objective: This research investigates how authentic leadership influences members' affective commitment at a charitable institution in Indonesia. Method: This study employed a quantitative approach using simple linear regression analysis with IBM SPSS version 23. The sample consisted of 110 active members from a population of 163, determined using the Isaac and Michael table at a 5% significance level. Variables were measured using authentic leadership and affective commitment scales. Results: Hypothesis testing there is an effect of authentic leadership on affective commitment with a regression coefficient value (R = 0.780) with a significance value of 0.000. While the R square value shows 0.608 which means that the effect of authentic leadership on affective commitment is 60.8%. Conclusion: Authentic leadership significantly shapes affective commitment in the institution. Abstrak Latar Belakang: Manajemen Sumber Daya Manusia (MSDM) masih menjadi tantangan bagi perusahaan dan organisasi, salah satunya adalah meningkatkan komitmen organisasi terhadap anggota yang berdampak pada keunggulan kompetitif dimana peran pemimpin sangat dibutuhkan untuk meningkatkan komitmen pada anggota. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh variabel kepemimpinan autentik terhadap komitmen afektif anggota di One Indonesian Charity Institution. Metode: Penelitian ini menggunakan pendekatan kuantitatif, dengan metode penelitian kuantitatif regresi linier. Analisis data dilakukan dengan menggunakan teknik regresi linier sederhana dengan IBM SPSS versi 23.0. Populasi sebanyak 163 anggota, dengan sampel 110 anggota aktif didapatkan melalui tabel Isaac dan Michael dengan signifikansi sebesar 5%. Variabel diukur dengan skala kepemimpinan autentik dan skala komitmen afektif. Hasil: Uji hipotesis terdapat pengaruh kepemimpinan autentik terhadap komitmen afektif dengan nilai koefisien regresi (R=0,780) dengan nilai signifikansi 0,000. Sedangkan nilai R square menunjukkan 0,608 yang berarti pengaruh kepemimpinan autentik terhadap komitmen afektif sebesar 60,8%. Kesimpulan: Sehingga disimpulkan terdapat pengaruh kepemimpinan autentik terhadap komitmen afektif yang kuat. Dimana kepemimpinan otentik menjadi kunci untuk membangun komitmen afektif terkhusus di One Indonesian Charity Institution.